Waiting Game: Exploring The Lived Experiences Of First Nations Who Are Waiting For Housing To Determine Appropriate Policy And Planning Directions - Catriona Moggach (10848879) (2021)
This Major Research Paper explores the lived experiences of Eabametoong and Nibinamik First Nations members while they wait for housing to determine how planning and policy can better address the challenges they identify. This period that can reach 10 years is marked with uncertainty and increased stress that negatively impacts quality of life, promotes overcrowding, and results in many members leaving their reserves. Understanding the impacts of waiting has not been studied in a First Nations context. The work of Oldfield and Greyling (2015) on waiting for housing in post- apartheid South Africa serves as a framework in which to analyze the lived experiences of Canada’s First Nations while they also wait for housing due to similar colonial pasts. As such, this paper presents waiting as the product of political inaction, and therefore a policy direction in its own right.